P126 The FLIP study – Fluid resuscitation In Pancreatitis. (8th April 2021) - Moir, John; Tingle, Sam; Hawthornthwaite, Emma; Robinson, Stuart; French, Jeremy; ,
Abstract: Introduction: Acute pancreatitis is a common condition encountered in emergency general surgical presentations. The severity of this condition can range from mild, whereby symptoms settle with simple conservative measures, to severe and potentially life threatening in up to 20% of cases. Intravenous fluids are the cornerstone of management in these patients, however there is very little guidance and poor quality evidence within the research literature regarding optimal intravenous fluid administration. The aim of this study is to establish current clinical practice within the North East of England regarding the rate of intravenous fluid administration in acute pancreatitis and the effect this has on patient morbidity and mortality. Methods: This project is a prospective multi-centre snapshot audit of patients presenting with acute pancreatitis over a one month period, with 30 days follow up. Inclusion criteria are patients aged 18 or above with acute pancreatitis. Data will be collected on intravenous fluid administration in the first 72 hrs following admission in addition to demographics and severity scoring. The primary outcome measure will be admission to HDU/ITU with key secondary end-points including 30-day mortality, length of stay, radiological evidence of pancreatic necrosis and evidence of organ failure. Results: The results of this study will be prepared in accordance with guidelines set by the STROBE: (Strengthening the Reporting of Observational Studies in Epidemiology) statement for observational studies. Data will be collected and analysed with appropriate statistical tests using SPSS. Statistical significance will be defined as a p value of ≤ 0.05 Conclusion: Data collection will be completed in early 2021 with analysis and write up planned for early in the new year. Pending the results of phase one, an RCT will be designed to determine the optimal rate of intravenous fluids for improved patient outcome.